2018
DOI: 10.1136/jmedgenet-2018-105272
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing analysis of CNV using low-coverage and paired-end strategies is efficient and outperforms array-based CNV analysis

Abstract: CNV analysis using low-coverage WGS is efficient and outperforms the array-based analysis that is currently used for clinical cytogenetics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 40 publications
4
73
0
Order By: Relevance
“…CNA supersedes that obtained by FISH, both in the number of abnormalities and specific genomic resolution, as expected from a nontargeted vs a targeted approach. Zhou et al demonstrated the superiority of LD-WGS over high-density oligonucleotide arrays in detecting germline CNAs, compared to even the least sensitive of their methods 16. These findings were also robust across multiple patients hence validate our results and demonstrate the benefit of using non-targeted genomic approach in studying the genetic constitution of MM.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…CNA supersedes that obtained by FISH, both in the number of abnormalities and specific genomic resolution, as expected from a nontargeted vs a targeted approach. Zhou et al demonstrated the superiority of LD-WGS over high-density oligonucleotide arrays in detecting germline CNAs, compared to even the least sensitive of their methods 16. These findings were also robust across multiple patients hence validate our results and demonstrate the benefit of using non-targeted genomic approach in studying the genetic constitution of MM.…”
supporting
confidence: 82%
“…Clearly, there is value of LD-WGS to not only fulfill the current clinical needs in MM, but to open doors for further exploratory potential in disease biology and therapeutics. Zhou et al demonstrated the superiority of LD-WGS over high-density oligonucleotide arrays in detecting germline CNAs, compared to even the least sensitive of their methods 16. The clinical utility of LD-WGS has been reported in other contexts; 7,8 however, to our knowledge, there have been no reports validating its use in hematological malignancies including those whose prognostic determination relies heavily on CNA detection such as MM.The revised International Staging System for risk stratification of MM is based on cytogenetic information obtained from FISH data 2.…”
mentioning
confidence: 99%
“…For downstream inference, these data are typically summarized by generating binned coverage profiles of the sequencing output, whereby the genome is uniformly partitioned into moderately sized contiguous regions (e.g., 10-50 kilobases (kb)) and count-based coverage is calculated by the enumerating the overlapping sequencing reads. Evidence of copy-number variants (CNVs) and aneuploidy may be detected from these profiles using standard CNV detection methods for coverage data 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In such scenarios, statistics-based segmentation [9, 14, 20] and CNV calling lead to either in false segmentation or missing the focal alterations. However, low-coverage NGS data is still more efficient than array-based data for CNV analysis [21].…”
Section: Introductionmentioning
confidence: 99%